2016
DOI: 10.1038/srep34334
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive ligand tether length affects the size and length of focal adhesions and influences cell spreading and attachment

Abstract: Cells are known to respond to physical cues from their microenvironment such as matrix rigidity. Discrete adhesive ligands within flexible strands of fibronectin connect cell surface integrins to the broader extracellular matrix and are thought to mediate mechanosensing through the cytoskeleton-integrin-ECM linkage. We set out to determine if adhesive ligand tether length is another physical cue that cells can sense. Substrates were covalently modified with adhesive arginylglycylaspartic acid (RGD) ligands cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 37 publications
4
59
0
Order By: Relevance
“…Primary culture-activated human hepatic stellate cells (passage 3-6, HHStec 5300; ScienCell, Carlsbad, CA, USA) were cultured at 37°C, 5% CO 2 in culture medium containing DMEM/Nutrient Mixture F-12 Ham (D8437; Sigma-Aldrich, St. Louis, MO, USA), 10% fetal bovine serum (10270-106; Thermo Fisher Scientific, Waltham, MA, USA), 1% penicillin/ streptomycin (Thermo Fisher Scientific), and 1% fungizone (15290-026; Thermo Fisher Scientific). Human foreskin fibroblasts (HFFs) were cultured in DMEM high glucose (D6429; Sigma-Aldrich) with the same supplements as previously described (16). For the polyacrylamide substrate experiments, cells were detached from culture flasks and transferred to 4, 12, 25 kPa single-rigidity or 4/25 kPa dual-rigidity polyacrylamide gels.…”
Section: Cell Culturementioning
confidence: 99%
“…Primary culture-activated human hepatic stellate cells (passage 3-6, HHStec 5300; ScienCell, Carlsbad, CA, USA) were cultured at 37°C, 5% CO 2 in culture medium containing DMEM/Nutrient Mixture F-12 Ham (D8437; Sigma-Aldrich, St. Louis, MO, USA), 10% fetal bovine serum (10270-106; Thermo Fisher Scientific, Waltham, MA, USA), 1% penicillin/ streptomycin (Thermo Fisher Scientific), and 1% fungizone (15290-026; Thermo Fisher Scientific). Human foreskin fibroblasts (HFFs) were cultured in DMEM high glucose (D6429; Sigma-Aldrich) with the same supplements as previously described (16). For the polyacrylamide substrate experiments, cells were detached from culture flasks and transferred to 4, 12, 25 kPa single-rigidity or 4/25 kPa dual-rigidity polyacrylamide gels.…”
Section: Cell Culturementioning
confidence: 99%
“…al. found that human foreskin fibroblasts attached to RGD ligands on glass also preferred short tethers; increasing adhesion and cell area correlated decreasing tether length [153]. …”
Section: Mechanobiology Of Adhesion Revealed Using Supported Lipidmentioning
confidence: 99%
“…Several parameters in the method of covalent tethering of peptides to a biomaterial surface influence the resulting functionality of the peptide. This includes, but is not limited to, the spacing between adhesive peptides, the length of the linker that is used to attach the peptide, and the amino‐acids that flank the essential peptide sequence, which all suggest that tuning the chemical nano‐environment of peptides is of great importance for functionality of the peptides. However, a popular approach features the functionalization with both bioactive peptides, and antifouling moieties, to enhance specificity of the bioactivation and reduce adhesion of undesired entities to the functionalized biomaterial, where the chemical environment of the peptides is designed to repel any aspecific interactions.…”
Section: Introductionmentioning
confidence: 99%